Osteonecrosis of the jaws related to medication use literature review (Research, Society and Development, 2022)
Bisphosphonates are pharmacological agents used in the treatment of osteoclast-mediated bone loss due to osteoporosis, Paget's disease, metastatic malignancies, with the adverse effect of their use being osteonecrosis. The objective of this work is to carry out a review of the literature on drug-induced osteonecrosis, evaluating its clinical, physiological and pharmacological characteristics. The research will be carried out through digital platforms such as: Llilacs, Pubmed, Scielo and Google scholar, with the following terms: osteonecrosis of the jaws, osteonecrosis by bisphosphonates, osteonecrosis, bisphosphonates, I have as a major focus complete works that address the topic in the form of a review gives literature or clinical case.